2021
DOI: 10.3390/educsci11050223
|View full text |Cite
|
Sign up to set email alerts
|

Doing Critical Language Teaching through Tasks: Insights from the Brazilian Context

Abstract: Although Brazilian governmental documents have conceived language teaching from a critical perspective, the recent scenario points to a backlash towards critical perspectives on teaching, which have been socially perceived as indoctrination. Since we understand critical pedagogy in additional language classrooms as a necessary emancipatory perspective, this article aims at discussing possibilities for promoting critical language development. More specifically, it draws on two doctoral studies in which teacher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Results revealed that deciding on target and pedagogical tasks and supporting tasks for beginners were two primary challenges that pointed to the essential roles of needs analysis and a clear instructional framework in using tasks. Farias et al (2021) were among the first to discuss the possibilities for promoting critical language development through tasks. The authors used two doctoral studies in which teacherresearchers implemented critical task cycles to promote critical language development by fostering elementary and high school students' reflections on gender issues.…”
Section: Language Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Results revealed that deciding on target and pedagogical tasks and supporting tasks for beginners were two primary challenges that pointed to the essential roles of needs analysis and a clear instructional framework in using tasks. Farias et al (2021) were among the first to discuss the possibilities for promoting critical language development through tasks. The authors used two doctoral studies in which teacherresearchers implemented critical task cycles to promote critical language development by fostering elementary and high school students' reflections on gender issues.…”
Section: Language Focusmentioning
confidence: 99%
“…More recent attention has focused on promoting critical language development through critical task cycles, emphasizing the affordances and challenges of promoting social transformation (FARIAS, et al, 2021). Further work is needed to determine whether Critical Language Teaching is possible in the various technology-mediated learning environments which emerged during social distancing caused by the Covid-19 pandemic.…”
Section: Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, I could have spent some time discussing what "safe space" might connote given its historical use and the debates around the term in the United States. This is part of critical vocabulary teaching [52], and can be integrated into critical language tasks [53]. While teaching the cultural-historical roots of the term may not have changed the teacher's use of it or intention in using it in the future, it could at least alert them to potential miscues that may occur when communicating with others, as the use of that term did for me index and prepare me for a different sort of discussion than what followed.…”
Section: Social Justice Aimsmentioning
confidence: 99%
“…A slight shift of focus, to language itself, takes us to Siqueira's consideration of English as a Lingua Franca [10] (which follows from critical language pedagogy's emphasis on critiquing the content of instruction itself), and somewhat relatedly, Parba's study of the role played by critical vocabulary in critical language teaching [11]. Both Cannizzo and Parba are also very much concerned with the classroom, and this is matched by the two papers focusing on classroom activities under the heading of tasks (Crookes and Ziegler [12]; Farias and da Silva, [13]). The first of these two asks about the engagement of critical language pedagogy with one other important tradition in second language curriculum (associated with the term "task"); the second shows how this may play out in materials and the classroom.…”
Section: The Articles Themselvesmentioning
confidence: 99%